The Contribution of Gi/o Protein to Opioid Antinociception in an Oxaliplatin-Induced Neuropathy Rat Model - Tomoe Kanbara; Atsushi Nakamura; Keiko Takasu; Koichi Ogawa; Masahiro Shibasaki; Tomohisa Mori; Tsutomu Suzuki; Minoru Hasegawa; Gaku Sakaguchi; Toshiyuki Kanemasa (Elsevier, 2014)
Abstract.: Oxaliplatin is a chemotherapeutic agent that induces chronic refractory neuropathy. To determine whether opioids effectively relieve this chronic neuropathy, we investigated the efficacies of morphine, oxycodone, and fentanyl, and the mechanisms underlying opioid antinociception, in oxaliplatin-induced neuropathy in rats. Rats exhibited significant mechanical allodynia following 2 weeks of chronic oxaliplatin administration. Within the range of doses that did not induce sedation and/or muscle rigidity, morphine (3 mg/kg, subcutaneously, s.c.) and oxycodone (0.3 - 0.56 mg/kg, s.c.) completely reversed oxaliplatin-induced mechanical allodynia, whereas fentanyl (0.017 - 0.03 mg/kg, s.c.) showed partial antinociception. The antinociception of the optimal doses of morphine and oxycodone were completely inhibited by pertussis toxin (PTX; 0.5 μg/rat, i.c.v.), a Gi/o protein inhibitor, while the partial effect of fentanyl was not affected in the oxaliplatin model. In the [35S]-GTPγS binding assay, activation of μ-opioid receptor by fentanyl, but not by morphine or oxycodone, in the mediodorsal thalamus was significantly reduced in oxaliplatin-treated rats. These results indicate that the lower antinociceptive potency of fentanyl in the oxaliplatin model might in part result from the loss of PTX-sensitive Gi/o protein activation, and the degree of Gi/o protein activation might be related to the potency of antinociception by opioids in this model. Keywords:: opioid, antinociception, oxaliplatin, neuropathy, Gi/o protein